2015
DOI: 10.1890/14-2113.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the landscape of fear between apex predatory sharks and mobile sea turtles across a large dynamic seascape

Abstract: Abstract. The ''landscape of fear'' model has been proposed as a unifying concept in ecology, describing, in part, how animals behave and move about in their environment. The basic model predicts that as an animal's landscape changes from low to high risk of predation, prey species will alter their behavior to risk avoidance. However, studies investigating and evaluating the landscape of fear model across large spatial scales (tens to hundreds of thousands of square kilometers) in dynamic, open, aquatic system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 50 publications
2
38
0
Order By: Relevance
“…Similarly, a new study evaluated predator-prey interactions between tiger sharks (Galeocerdo cuvier) and loggerhead turtles (Caretta caretta) by testing for differences in their surfacing behaviour (derived from the frequency of Argos messages received from satellite tags, as in our study) in and out of home range overlap areas [26]. The wider implications of our study are that blue sharks may be more vulnerable to bycatch from surface longlines during the twilight periods.…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, a new study evaluated predator-prey interactions between tiger sharks (Galeocerdo cuvier) and loggerhead turtles (Caretta caretta) by testing for differences in their surfacing behaviour (derived from the frequency of Argos messages received from satellite tags, as in our study) in and out of home range overlap areas [26]. The wider implications of our study are that blue sharks may be more vulnerable to bycatch from surface longlines during the twilight periods.…”
Section: Discussionmentioning
confidence: 88%
“…As such, we cannot conclude that our data is representative of the entire population within the region. For tiger sharks, individuals tagged in the Florida and Bahamas study sites generally showed similar residency and home range patterns (Hammerschlag et al ., , ). However, it would be valuable to include data from tagging efforts across various sites of the tropical and subtropical Atlantic.…”
Section: Discussionmentioning
confidence: 97%
“…Movements of turtles can be linked with predation (Heithaus et al 2008, Hammerschlag et al 2015, environmental change (Pike 2008, Schofield et al 2009), or anthropogenic pressure, to distinguish what factors affect turtle foraging, migration, and development (Taquet et al 2006, Heithaus 2013. While our study has provided valuable data regarding the movements of juvenile hawksbill turtles around an offshore developmental habitat, other methods of long-term monitoring, such as satellite telemetry and stable isotope analysis, would permit insights even if tracked individuals were to leave the atoll (Shimada et al 2014).…”
Section: Future Directionsmentioning
confidence: 99%